Euphemism And Social Prejudice In The 2024 Presidential Debate: Anies’s Rhetoric Toward Prabowo - Inayatur Rosyidah; Bisri Mustofa; Muhamad Rofik Fitrotulloh; Efy S.Atanjuani (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to identify and analyze euphemistic expressions that reflect social prejudice in the 2024 Indonesian presidential debate, specifically those used by Anies Baswedan in reference to Prabowo Subianto. The study is significant in revealing how linguistic strategies are employed in political communication to deliver implicit yet ideologically charged criticism. Adopting a qualitative descriptive method within an ethnocommunicative framework, data were collected through passive participatory observation, note-taking, and documentation of debate recordings and transcripts. The data were analyzed using content analysis in five stages: problem formulation, theoretical framework development, methodological design, application of analytical techniques (classification, semantic interpretation, and contextual inference), and conclusion drawing. The findings reveal that Anies Baswedan employed three types of euphemism—underspecification, overstatement, and understatement (litotes)—to express negative evaluations containing various forms of social prejudice, including stereotyping, social judgment, and antilocution.